Employment initiatives for an ageing workforce in the EU 15 - Taylor, Philip (Luxembourg, 2006)
"As the European population grows older, there is increasing pressure on governments and companies to provide initiatives that enable and encourage older workers to remain in the workplace. This report documents a range of case examples from companies across the former 15 EU Member States which have implemented successful age management initiatives over the past ten years. The 150 examples selected demonstrate good practice in such areas as recruitment, training, skills development, time management, health promotion and workplace design. The overall aim of the research was to show effective ways of increasing the labour market participation of older workers, to enhance their contribution and productivity, and to prevent the incidence of early exit and unemployment."